Transformação genética de Urochloa brizantha para tolerância ao déficit hídrico e validação de genes normalizadores para estresses abióticos - Takamori, Luciana Midori (2018)
Brachiaria grass comes from Africa and belongs to the genus Urochloa. The U. brizantha is tetraploid and apomictic and is the species more cultivated in Brazil, being used for both animal feeding and vegetation cover. Extensive pasture areas are cultivated with few cultivars due to a lack of genetic improvement of this species. Genetic transformation is an important tool for introducing genes with desirable agronomic traits. However, there are still no transgenic cultivars for the species of the genus Urochloa. The aim of this work was to develop a protocol to engineer genetically modified Urochloa plants by biobalistic delivery system. Three types of explants were tested: epicotyl, calli from epicotyl and seed pre-inoculated for 5 days in MS medium containing 2,4-D auxin or picloram (1 mg L-1). The distances of 3, 6, 9 and 12 cm from the microcarrier to the explant, and the particle concentration 30 or 60 mg.ml-1. The pANIC6E vector and the pressure of 1100 psi were used to evaluate the transient expression of the uidA gene. The highest expression of the uidA gene was observed when calluses induced from seeds were bombarded at the distance of six cm and at the concentration of 60 mg.ml-1 of gold particles. After determining the best parameters, calli derived from seeds were bombarded with the pJS107 vector which contains the p5cs (Δ1 - pyrroline - 5 - carboxylate synthetase) and the bar genes. Bombarded calli were cultured in a selective medium containing 2 mg L-1 of ammonium glufosinate. A total of 91 seedlings were regenerated in vitro. The plantlets were acclimatized in greenhouse and submitted to PCR analysis. A total of 79 plants were analyzed. Fragments corresponding to the bar (450 bp) and the p5cs (580 bp) genes were amplified in 21 and 13 plants, respectively. Only 8 plants present the fragments corresponding to the two genes. The transformation efficiency was 0.32%. Transgenic events and control plants (untransformed) were submitted to water deficit (-2.9 to -3.4 MPa) and the proline concentration in the leaves was determined. The transgenic events presented up to 1.9 times more proline than the control plant in conditions of water stress. Chapter 2 of this thesis refers to the validation of the normalizing genes for abiotic stresses (cold, heat and dry) in U. brizantha. The stability of nine reference genes: Actin 12, eukaryotic initiation factor 4A, alpha elongation factor-1, FTSH protease 4, U2 helper factor, succinol coenzyme A, tubulin alpha-5, tubulin beta-6, ubiquitin conjugated enzyme. Expression of the reference genes was measured by RTqPCR in leaf samples submitted to 6, 12 and 24 h of cold and heat (10 and 45 ° C respectively) and to moderate water deficit (-0.5 to -0, 7 Mpa), severe (-1.1 to -1.8 MPa) and recovered after irrigation. The RefFinder program was used to classify the most stable reference genes in each stress. The elongation factor-1 alpha, the ubiquitin conjugated enzyme or elongation factor-1 alpha, and the eukaryotic initiation factor 4A were the most stable genes for the heat stresses, cold and dry, respectively. The expression of the Rubisco gene was normalized against the most stable gene selected by RefFinder for each stress for validation.